Bank and Nonbank Financial Intermediation - BOND, PHILIP (Journal of Finance, 2004)
ABSTRACT Conglomerates, trade credit arrangements, and banks are all instances of financial intermediation. However, these institutions differ significantly in the extent to which the projects financed absorb aggregate intermediary risk, in whether or not intermediation is carried out by a financial specialist, in the type of projects they fund and in the type of claims they issue to investors. The paper develops a simple unified model that both accounts for the continued coexistence of these different forms of intermediation, and explains why they differ. Specific applications to conglomerate firms, trade credit, and banking are discussed.